2021
DOI: 10.21037/apm-21-208
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and clinical features of calcaneus osteomyelitis following calcaneus fracture: a retrospective study of 127 cases

Abstract: Background: To analyze the epidemiology and features of calcaneus osteomyelitis following open reduction and internal fixation (ORIF) after closed calcaneus fracture.Methods: We retrospectively analyzed 127 cases who were diagnosed with calcaneal osteomyelitis following ORIF via the extended lateral "L-shaped" approach after closed calcaneus fracture between March 2016 and August 2019 in our hospital. We analyzed participant demographics including gender, age, body mass index (BMI), trauma mechanism, Sanders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… 6 In that cohort, the ratios of the females patients with diabetic-foot OM (DFOM) and post-traumatic OM (PTOM) were 39.1% and 17.2%, with the median ages at diagnosis being 62 years (DFOM) and 38 years (PTOM), respectively. Among the included studies analyzing TRCO, the investigation with the largest sample size (127 patients) was reported by Huang et al, 15 who summarized clinical features of TRCO. They concluded that young (mean age: 46.8 years) and males (male/female = 4.47) were dominated, which was in line with our results (TRCO: median age: 44 years, male/female = 3.12).…”
Section: Discussionmentioning
confidence: 99%
“… 6 In that cohort, the ratios of the females patients with diabetic-foot OM (DFOM) and post-traumatic OM (PTOM) were 39.1% and 17.2%, with the median ages at diagnosis being 62 years (DFOM) and 38 years (PTOM), respectively. Among the included studies analyzing TRCO, the investigation with the largest sample size (127 patients) was reported by Huang et al, 15 who summarized clinical features of TRCO. They concluded that young (mean age: 46.8 years) and males (male/female = 4.47) were dominated, which was in line with our results (TRCO: median age: 44 years, male/female = 3.12).…”
Section: Discussionmentioning
confidence: 99%
“…The weight bearing surface of the heel is prone to fracture-related infections, penetrating injury, and pressure ulceration, particularly in the context of peripheral neuropathy. 15 , 16 The fundamental steps in treating chronic osteomyelitis include physiological optimization of the patient, a thorough debridement of poorly vascularized and infected bone, dead space management, ensuring skeletal stability, appropriate antibiotics based on careful intraoperative sampling, and adequate soft tissue coverage. 11 Accomplishing these objectives can be difficult when there is extensive osteomyelitis of the calcaneus.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of open calcaneal fractures, the complication rate increases by 5 to 7 times. 15 , 16 , 33 Many authors have noted that in open calcaneal fractures, infection can affect up to 60% of cases, sometimes necessitating amputations, with postoperative infections affecting up to 25% of patients. 6 , 14 , 42 As Morgenstern et al 32 have noted, there are currently no specific diagnostic criteria for fracture-related infections.…”
Section: Introductionmentioning
confidence: 99%